Pembuatan Game Cerita Rakyat Dengan Bentuk Adventure Game - Tjahjono, Harvey; Liliana, Liliana; Gunadi, Kartika (Jurnal Infra, 2015)
These days traditional thing has been left behind not only by adults but also by children. One of them is folklore. It disappears because its package cannot interest the people. It needs a better package that interests a lot of people, for example game. The game in this thesis took folklore theme that would teach the children about morale values. This game was made based on PC game because electronic device are increasingly in demand and with adventure game-based which is a game genre that a lot of people like including the children.This game was made by Unity3D which is can place the objects that we use easier. Besides, camera setting which is a feature of Unity3D can make the setting of the 2D graphics easier. First of all, the folklores need to be parted into the playable-part and the non-playable-part. In playable-part, the player needs to solve some tasks to play the next folklore. In non-playable-part, the game will show an animation.This folklore game can interests the children to become a better person from the morale value. But, it is hard to implement folklore into adventure game for some folklores. For example Origin of Mahakam Riverâs Creek that has some complicated detail to express the setting of the story.